The physiological and pathophysiological aspects of the human cochlea: a review - Munjal, Manish; Munjal, Shubham; Kaur, Hardeep; Arora, Vineeta; Randev, Aditi; Jeriwal, Sakshi; Bharadwaj, Prachi; Mittal, Namit; Mittal, Navya; Pillai, Anjana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
The fluids of the membranous labyrinth are in a state of dynamic equilibrium with the intracranial cerebrospinal fluid. Mechanical shifts in the ear canal, middle and inner ear due to tympanic, ossicular, and basilar membrane displacements are likely to result in electrolyte alterations with the generation of nerve impulses. Sound wave, depending on its frequency, attains maximum amplitude at a particular site on the basilar membrane and stimulates that very segment. Higher frequencies are represented at the basal turn of the cochlea, and the progressively lower ones towards the apex. The disturbance in the milieu interior is consequent to auditory and vestibular impairments. Physiology of the cochlea is altered in varied conditions like hypertension, renal disease, syphilis, chronic suppurative otitis media, diabetes, and noise trauma. The unique physio-pathology of the membranous labyrinth shall be elaborated.